Development of Learning Media Moodle-Based on Static Fluids - Halimatush S.T Utari; Rini Budiharti; Sukarmin Sukarmin; Daru Wahyuningsih; Fairusy F Haryani (Postgraduate, University of Mataram, 2023)
The purpose of this study was to develop a physics learning media Moodle-based with a scientific approach to static fluid that is feasible to use in the learning process. Previous research found that the media developed did not contain simulations which are very necessary in learning physics. Therefore, it is necessary to develop media that supports simulating physics practicums, especially in static fluids, and interactive. This study used the research and development (RnD) method, with the model ADDIE. However, because the goal was only to get the feasibility of the media, the steps were limited to three stages, which were Analyze, Design, and Development. This media is equipped with simulations using PhET and another Virtual Laboratory which can be accessed online through belajarsains-uns.com. The result is that the physics learning media Moodle-based on static fluids was successfully developed with very good criteria based on the assessments from expert validators, peer reviewers, and reviewers around 1364 of 1476. Meanwhile, during trials, some errors are found in the spelling of sentences. After revising, an increased score of the pre-test and post-test showed that learning media was effectively used and the questionnaire result met very good criteria, 5728 of 6840